Pengaruh Keprofesionalan Guru Dalam Meningkatkan Pendidikan Akademik dan Karakter Siswa di Sekolah - Arya Tantri; Faradilla Amelia; Siti Syevila; Siti Hanifah Hanum; Tamimi Mujahid; Aliyah Putri Azzahra; Ok Reza Fathurrahman (Jurnal Ilmiah Wahana Pendidikan, 2022)
Teaching is a profession that demands special abilities and expertise obtained by certain education and training in its field. Profession can only be said if the teacher has met the requirements as a profession, then the teacher can be classified as a profession. Teachers have a huge responsibility and have a direct influence on the achievement of educational goals. Becoming a professional teacher is not easy. A teacher must have and give dedication to this work. If not, then the purpose of education which is closely related to the formation of the quality of human resources will not be achieved. The teaching profession is required to be able to work optimally in educating students so that education does not fail. Teacher professionalism can improve academic education and student character. Professional teachers are teachers who want to prioritize the quality and quality of their services and products, teacher services must meet standards such as personality competencies, managerial competencies, entrepreneurial competencies, supervisory competencies, and social competencies. As well as maximizing the ability of students based on the potential and skills possessed by each individual to become better. The purpose of this study is to identify and examine: 1) teacher professional development strategies 2) the role of professional educators in academic development and student character 3) professional educator performance.